Breastfeeding mother's experiences with breastfeeding counselling: a qualitative study - Ingvild Lande Hamnøy; Marianne Kjelsvik; Anne Bergljot Baerug; Berit Misund Dahl (BMC, 2024)
Abstract Background Mothers are recommended to breastfeed their children but can find it challenging and experience breastfeeding problems. Qualified breastfeeding counselling from healthcare professionals can help mothers master breastfeeding, but there is a need to explore mothers' lived experiences with receiving breastfeeding counselling. We aimed to reveal breastfeeding mothers' experiences with receiving breastfeeding counselling from midwives and public health nurses (PHNs) to provide a deeper insight into the phenomenon of breastfeeding counselling, which may improve breastfeeding counselling in practice. Methods A qualitative design with a hermeneutic phenomenological approach was used. Individual interviews of 11 breastfeeding mothers from Norway were conducted from September 2021 to 2022. Van Manen's guided existential inquiry guided the reflective process to provide deeper insights into the phenomenon of breastfeeding counselling. Results The study captured the meaning of breastfeeding mothers' lived experiences with breastfeeding counselling. Three themes and eight sub-themes were found. Breastfeeding was at stake for the mothers because breastfeeding could be reduced or stopped, and qualified breastfeeding counselling from midwives and PHNs was essential for them to establish and continue breastfeeding. They needed to be perceived as both breastfeeding mothers and as women with their own needs to master everyday life during the breastfeeding period. Conclusions This study offers insights to midwives, PHNs and others offering breastfeeding counselling by facilitating an understanding of being a breastfeeding mother receiving breastfeeding counselling. Qualified breastfeeding counselling and a trusting relationship with midwives and PHNs are essential for mothers to establish and continue breastfeeding, while deficient counselling may cause breastfeeding difficulties. Mothers need to be treated as whole and competent persons to avoid objectification and fathers/partners need to be included in breastfeeding counselling. The 'Baby-Friendly Hospital Initiative' should be continued, and guidelines should align with the mothers' need to incorporate breastfeeding into their daily lives during the breastfeeding period.